2007
DOI: 10.1507/endocrj.k07-031
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Ghrelin, Leptin, IGF-I, IGFBP-3, Insulin, Thyroid Hormones and Cortisol in Prepubertal Children with Iron Deficiency

Abstract: Abstract. The aim of the present study is to investigate possible alterations in ghrelin and other hormone levels related to appetite and somatic growth in children with iron deficiency anemia. Twenty-five patients and 25 healthy controls that were prepubertal and within normal limits regarding height and BMI standard deviation scores were recruited. Ghrelin, leptin, IGF-I, IGFBP-3, insulin, thyroid hormones and cortisol levels were studied. Ghrelin, insulin and IGF-I levels were significantly low in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 28 publications
(30 reference statements)
3
27
1
5
Order By: Relevance
“…The study "Serum Levels of Ghrelin, Leptin, IGF-I, IGFBP-3, Insulin, Thyroid Hormones and Cortisol in Prepubertal Children with Iron Deficiency" authored by İsgüven et al was published in Endocrine Journal in 2007 [1]. We read the article with great interest.…”
Section: Dear Editor;mentioning
confidence: 98%
“…The study "Serum Levels of Ghrelin, Leptin, IGF-I, IGFBP-3, Insulin, Thyroid Hormones and Cortisol in Prepubertal Children with Iron Deficiency" authored by İsgüven et al was published in Endocrine Journal in 2007 [1]. We read the article with great interest.…”
Section: Dear Editor;mentioning
confidence: 98%
“…In the study of Firczyk et al, the average duration of hemodialysis in the hemodialysis with diabetic nephropathy group was 28 months and in the hemodialysis patients without nephropathy was 25 months (19). Furthermore, in the study by Isguven et al in 2007, among the children suffering from iron deficiency anemia, the ghrelin levels were significantly lower than the control group, but no clear association between the ghrelin levels and their blood parameters was found (17). In our study, the ghrelin levels of non-diabetic hemodialysis patients showed a positive and not significant correlation with their hemoglobin levels.…”
Section: Discussionmentioning
confidence: 96%
“…Ayala et al reported a significant relationship between the baseline serum levels of ghrelin and serum insulin levels, body mass index (BMI), abdominal fat and serum leptin levels (16). Furthermore, Isguven et al studied ghrelin levels in children suffering from anemia and reported that ghrelin level was significantly lower than normal individuals (17). In another study on menopausal women, the serum ghrelin levels were found to be lower than non-menopausal healthy individuals with a significant relationship between serum ghrelin and bone density (18).…”
mentioning
confidence: 99%
“…Further more recently, Isguven et al [6] and Akarsu et al [7] reported that total ghrelin decreased with IDA and concluded that appetite loss in iron deficiency is a result of decrement of appetite hormone ghrelin [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies showed that obestatin was also involved in inhibiting thirst, improving memory, and affecting cell proliferation (reviewed [24]). As indicated above, ghrelin and obestatin might play crucial role or roles in a quite diverse range of physiologic functions in diseases, including IDA Since it has been shown that ghrelin decreased in children with IDA, it was concluded that loss of appetite was a result of decreased ghrelin [6,7]. However, both groups in those studies [6,7], they measured only total ghrelin in children with IDA and did not follow up by iron supplementation, whereas appetite stimulation could be achieved with acylated ghrelin [21].…”
Section: Introductionmentioning
confidence: 99%